Long‐Term Clinical Outcomes and Pain Assessment after Posterior Lumbar Interbody Fusion for Recurrent Lumbar Disc Herniation. Issue 3 (3rd June 2020) - Yang, Yalin; Yan, Xu; Li, Wenhui; Sun, Weizong; Wang, Kai
Abstract : Objectives: The aim of this study was to investigate the long term effects of posterior lumbar interbody fusion (PLIF), applied after recurrent lumbar disc herniation (rLDH), on pain relief and clinical outcome improvement. Methods: The current study is a retrospective study. We observed 22 cases from 85 patients that had undergone PLIF during February 2003 to October 2012 and all patients were followed for at least 5 years. The average age of those patients were 53 years, among them there were eight men and 14 women. Plain radiography and dynamic plain films were obtained, pre‐operation, for every patient. Magnetic resonance imaging (MRI) or computed tomography (CT) was conducted to confirm the diagnosis of rLDH before the operation. All surgeries were performed from posterior approach by the same surgeon using PLIF. Quality of life (QOL) and clinical outcomes were assessed by Numerical Rating Scale (NRS), Japanese Orthopaedic Association (JOA) scoring system, and Oswestry Disability Index (ODI) before revision surgery and at 1 week, 3 months, 12 months, and 24 months postoperative. These were also examined every time they came back to the hospital for a review. Results: All patients were discharged and no serious comorbidities occurred. Three cases with wound infections and one case with dural laceration were cured and discharged. The end point of follow‐up was August 2018 and the mean follow‐up after revision surgery was 85 months. There were significant differences in NRS. It decreased from 7.32 ± 1.17 to 2.77 ± 1.31 ( P  < 0.05). The mean postoperative NRS score was 2.27 ± 1.48 ( P  < 0.05), 1.90 ± 1.51 ( P  < 0.05), and 2.36 ± 1.36 ( P  < 0.05) at 3, 12, and 24 months after surgery. There were no statistically significant differences ( P  > 0.05) in ODI scores. The average JOA score improved from 5.00 ± 1.08 to 8.18 ± 1.59 ( P  < 0.05) 1 week after revision surgery. RR was between 50% and 70%. Overall satisfaction rates were beyond 80%. Only one patient required subsequent lumber surgery during the follow‐up period. Conclusion: If surgical indications are mastered, undergoing PLIF after rLDH may induce efficient pain relief and major improvements in clinical outcome scores, as well as quality of life scores.